Placental mesenchymal dysplasia - morphology and differential diagnosis - Daumová, Magdaléna; Hadravská, Šárka; Peteříková, Andrea Straková; Hasch, Marcel; Martínek, Petr (Ceskoslovenska patologie, 2021)
Placental mesenchymal dysplasia is a rare placental lesion characterized by placentomegaly, vascular abnormalities and formation of cystic structures in the placental parenchyma. It can be associated with various genetic abnormalities, fetal growth restriction or intrauterine fetal demise. Placental mesenchymal dysplasia needs to be distinguished from its main differential diagnosis, partial hydatidiform mole. The aim of this article is to provide readers with a basic overview of the morphology and differential diagnosis of this pathological entity.
Keywords: cystic lesions; placenta; Fetal Growth Retardation; nemoci placenty; Humans; Female; lidé; mola hydatidosa; ženské pohlaví; nádory dělohy; těhotenství; PMD; Placenta Diseases; Hydatidiform Mole; Placenta; differential diagnosis; růstová retardace plodu; placental mesenchymal dysplasia; Uterine Neoplasms; Diagnosis, Differential; Pregnancy; diferenciální diagnóza